INNOVATION PROJECT VALUE ASSESSMENT METHODOLOGY FOR HIGH-TECH ENTERPRISES - M. A. Kosukhina (Дискурс)
Presents a hierarchical model of methodology selection for assessing the value of high-tech enterprises innovative projects, which allows selecting a technique based on the required to it criteria. The techniques of innovative projects valuation, features of high-tech enterprises innovative projects are observed. The method of innovative projects valuation based on fuzzy logic is developed.